Двобічні об’ємні утворення надниркових залоз - Черенько, С. М.; Ларін, О. С.; Товкай, О. А. (Clinical Endocrinology and Endocrine Surgery, 2013)
Comprehensive analysis of various causes of bilateral tumorous or hyperplastic adrenal masses, including incidence, structure, and clinical course was done in the article. The topic was illustrated by literature review and own experience of 129 patients. The relevant management algorithm was proposed